Analisis Teknologi Informasi Dan Knowledge Haring Terhadap Kinerja Karyawan Koperasi Simpan Pinjam Bhina Raharja Cabang Kragan - Abdil Jinan; Ming Ming Lukiarti (Universitas Islam Kadiri, 2023)
The purpose of this study was to prove the partial effect of each variable of information technology and knowledge sharing on the performance of KSP Bhina ​​Raharja Kragan Branch employees. The research population is KSP Bhina ​​employees, totaling 58 people. The test results show that information technology has no significant positive effect on employee performance, while knowledge sharing has a significant positive effect on employee performance. The results of the determination test showed an adjusted R square value of 0.210, meaning that the independent variables in this study, namely information technology and knowledge sharing, were only able to explain the dependent variable, namely employee performance by 21%, while 79% was explained by other variables outside this study.